1978
DOI: 10.1086/268439
|View full text |Cite
|
Sign up to set email alerts
|

Newspapers, Television and Political Reasoning

Abstract: OF THE most powerful hopes advanced by theories of representative government is that news media remain free so they may educate the public in making political choices. Ignorance condemns people to sway with the most available rhetoric. The uninformed person chooses randomly or out of habit to support candidates or policies. 1 Often he or she avoids the political arena altogetherperhaps because of hedonism or alienation. 2 1 An analogy to this point, drawn from laws of inertia, can be found in Converse (1962). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(31 citation statements)
references
References 10 publications
0
31
0
Order By: Relevance
“…Much news research focuses on knowledge gain because news is designed to inform the public (e.g., Clarke & Fredin, 1978). This research observed that knowledge gain is associated with an informational orientation toward the news and higher levels of cognitive involvement.…”
Section: Local Television Newsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much news research focuses on knowledge gain because news is designed to inform the public (e.g., Clarke & Fredin, 1978). This research observed that knowledge gain is associated with an informational orientation toward the news and higher levels of cognitive involvement.…”
Section: Local Television Newsmentioning
confidence: 99%
“…Information holding measures do not concentrate on facts, but allow respondents to focus on issues that are important to themselves rather than on issues that are important to researchers (Roberts & Maccoby, 1985). Although information holding research has not focused on cognitive activity, information holding is associated with message discrimination, or recalled messages about issues (Clarke & Fredin, 1978;Clarke & Kline, 1974). Recalled messages are usually associated with focused attention and cognitive effort (Greenwald & Leavitt, 1984).…”
Section: Local Television Newsmentioning
confidence: 99%
“…As elaborated earlier by Clarke and Fredin (1978) and Miller, Goldenberg and Erbring (1979), papers do have an influence in peoples' beliefs. Furthermore, beliefs have been found to be rooted in the activities related to witchcraft (Davies, 1998).…”
Section: Implications To Science Teachingmentioning
confidence: 67%
“…Thus, newspapers have at least the potential to encourage reflexive absorption of information. For example, Clarke and Fredin (1978) have shown that political information filtered through newspapers is more likely to lead to reasoned electoral decisions. Or, as Sheley and Ashkins (1981) have shown, newspapers are relatively less likely to distort the extent and gravity of violent crime in urban areas.…”
Section: Mass Media and Spatial Fear: Theoretical Assumptions And Resmentioning
confidence: 99%